KONSEP AKAL BERTINGKAT AL-FARABI DALAM PERSPEKTIF NEUROSAINS DAN RELEVANSINYA DENGAN PEMBELAJARAN SAINS DI MADRASAH - Suntoro, Ranu (Risâlah, Jurnal Pendidikan dan Studi Islam, 2020)
Al-Farabi is a leading Muslim scientist and philosopher, his thoughts were widely referred by various groups, especially in the academic sphere with various disciplines. His philosophical thinking was much influenced by Greek philosophical thought. One of Al-Farabi's philosophical thoughts which is still relevant to be studied is about the concept of multilevel reasoning, where Al-Farabi conceptualizes the mind into ten levels. Al-Farabi's thinking about multilevel reasoning is still little studied in the perceptive neuroscience even more so its relevance to science education in Madrasas. In this study explains the concept of multilevel reasoning in the perspective of neuroscience and its relevance to science learning in Madrasas.